Roman military brick stamps on the Danubian limes in Croatia - Matijević, Vinka (2015)
The Croatian part of the Danube limes covers an area of 188 km along the river Danube from Batina Skela (Ad Militare) to Ilok (Cuccium). This is the area of Roman military fortresses where a large quantity of Roman construction material has been found. It includes some pottery, coins and bricks with stamps of military units. This poster represents bricks that were found at the sites Batina Skela (Ad Militare), Zmajevac (Ad Novas), Osijek (Mursa), Petrijevci (Mursella), Nemetin (Ad Labores), Sotin (Cornacum), Dalj (Teutoburgium) and Ilok (Cuccium). These brick findings tell us about the presence of military units in the Croatian part of the limes.
Projekt MZOS
ENG